2022
DOI: 10.31004/cendekia.v6i1.1139
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Bahan Ajar Matematika dengan Pemanfaatan Geogebra

Abstract: Bahan ajar ialah salah satu komponen sangat berarti dalam proses pembelajaran. Bahan ajar yang cocok dengan kebutuhan mahasiswa bisa menunjang pembelajaran jadi lebih efisien. Tujuan dari penelitian ini adalah untuk menghasilkan bahan ajar matematika dengan pemanfaatan geogebra yang valid dan praktis. Penelitian ini termasuk dalam penelitian pengembangan. Prosedur penelitian ini, mengacu pada pengembangan ADDIE (Analysis, Design, Development, Implementation, Evaluation). Sampel yang diambil dalam penelitian ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…The integration of ICT into the learning process can be realized by presenting innovative ICT-based teaching materials that have not previously been developed in schools. Considering that innovation through the integration of ICT into the learning process is also aimed at preparing human resources that can compete in the current global era (Permana P & Manurung, 2020;Wahyuni et al, 2022), because through the integration of ICT into learning aspects, has been shown to be able to contribute positively to the development and quality of education (Hoerunnisa et al, 2019;Siregar & Marpaung, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The integration of ICT into the learning process can be realized by presenting innovative ICT-based teaching materials that have not previously been developed in schools. Considering that innovation through the integration of ICT into the learning process is also aimed at preparing human resources that can compete in the current global era (Permana P & Manurung, 2020;Wahyuni et al, 2022), because through the integration of ICT into learning aspects, has been shown to be able to contribute positively to the development and quality of education (Hoerunnisa et al, 2019;Siregar & Marpaung, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Secara keseluruhan bahan ajar yang dikembangkan memperoleh skor rata-rata 88,30% berada pada kategori sangat valid. Hasil ini menunjukkan bahwa bahan ajar yang dikembangkan dinilai baik serta sudah layak digunakan dalam pembelajaran matematika, sebagaimana pernyataan (Wahyuni, Edrizon, & Fauziah, 2022) yang mengemukakan jika bahan ajar sudah memenuhi kriteria valid, maka dapat diuji cobakan.…”
Section: |unclassified
“…Teaching materials are a set of learning tools or tools that contain learning materials, methods, limitations and ways of evaluating that are designed systematically and attractively in order to achieve the expected goals, namely achieving competencies or sub-competencies with all their complexity (Dafit & Mustika, 2021;Wahyuni et al, 2022). So that teaching materials have an important role in learning.…”
Section: Introductionmentioning
confidence: 99%